2023
DOI: 10.11124/jbies-22-00367
|View full text |Cite
|
Sign up to set email alerts
|

Individual and environmental factors that influence longevity of newcomers to nursing and midwifery: a scoping review

Janie Alison Brown,
Tanya Capper,
Desley Hegney
et al.

Abstract: Objective: The objective of this review was to identify the literature and map the individual and environmental factors that influence registered nurses’ and midwives’ decision to stay or leave their professions within the first 3 years of practice. Introduction: Nursing and midwifery workforce sustainability is an international concern. One aspect is the retention of new registered nurses and midwives in their first years of practice. Several factors a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 79 publications
0
3
0
Order By: Relevance
“…Studies indicate that turnover rates among nurses may exceed 40%, and are particularly evident in those with less than three years' postgraduate experience. 2,3 For instance, a 2013 cross-sectional study conducted across 10 European countries found that 9% of the nurses intended to leave the profession, ranging from 5% to 17% across different countries. 4 A scoping review in this issue of JBI Evidence Synthesis identifies the individual and environmental factors that influence registered nurses' and midwives' decisions to stay or leave their professions.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Studies indicate that turnover rates among nurses may exceed 40%, and are particularly evident in those with less than three years' postgraduate experience. 2,3 For instance, a 2013 cross-sectional study conducted across 10 European countries found that 9% of the nurses intended to leave the profession, ranging from 5% to 17% across different countries. 4 A scoping review in this issue of JBI Evidence Synthesis identifies the individual and environmental factors that influence registered nurses' and midwives' decisions to stay or leave their professions.…”
mentioning
confidence: 99%
“…4 A scoping review in this issue of JBI Evidence Synthesis identifies the individual and environmental factors that influence registered nurses' and midwives' decisions to stay or leave their professions. 3 The review reveals that factors such as professional self-image, identity, pride in the profession, support from nurse managers, and the transition from academia to practice are crucial for retaining newly qualified professionals. 3 Another recently published review highlights the primary factors influencing newly graduated registered nurses' intention to leave: demographic variables (eg, age, educational level, years of experience, professional title, employment status, health status,…”
mentioning
confidence: 99%
See 1 more Smart Citation